(untitled) (Revista Apotheke, 2022)
This article presents the group “Caixa de Pandora: Estudos sobre Gênero, Arte e Memória” (CNPq), exploring its extensionist actions within the community, which seek to establish a dialogue about gender violence and stereotypes, as well as feminist alternatives to live and create. Textile arts were chosen by the group as a practice for our workshops because they have been culturally associated with the feminine since the Renaissance, artisanship arts that, contemporarily, are finding great appreciation within the arts. In these workshops, we collaboratively experimented with crochet, knitting and embroidery techniques, guiding gender discussions based in the experiences shared by the participants. Through the experiments and discussions carried out in the workshop, we seek to deconstruct the hegemonically patriarchal and European canon in art and literature to emphasize and highlight the dissident bodies.